Genomic Organization of Repetitive DNA Elements and Extensive Karyotype Diversity of Silurid Catfishes (Teleostei: Siluriformes): A Comparative Cytogenetic Approach - Ditcharoen, Sukhonthip; Antonio Carlos Bertollo, Luiz; Ráb, Petr; Hnátková, Eva; Franco Molina, Wagner; Liehr, Thomas; Tanomtong, Alongklod; Triantaphyllidis, Costas; Ozouf-Costaz, Catherine; Tongnunui, Sampan; Pengseng, Puan; Supiwong, Weerayuth; et al. (International journal of molecular sciences, 2019)
The catfish family Siluridae contains 107 described species distributed in Asia, but with some distributed in Europe. In this study, karyotypes and other chromosomal characteristics of 15 species from eight genera were examined using conventional and molecular cytogenetic protocols. Our results showed the diploid number (2n) to be highly divergent among species, ranging from 2n = 40 to 92, with the modal frequency comprising 56 to 64 chromosomes. Accordingly, the ratio of uni- and bi-armed chromosomes is also highly variable, thus suggesting extensive chromosomal rearrangements. Only one chromosome pair bearing major rDNA sites occurs in most species, except for Wallago micropogon, Ompok siluroides, and Kryptoterus giminus with two; and Silurichthys phaiosoma with five such pairs. In contrast, chromosomes bearing 5S rDNA sites range from one to as high as nine pairs among the species. Comparative genomic hybridization (CGH) experiments evidenced large genomic divergence, even between congeneric species. As a whole, we conclude that karyotype features and chromosomal diversity of the silurid catfishes are unusually extensive, but parallel some other catfish lineages and primary freshwater fish groups, thus making silurids an important model for investigating the evolutionary dynamics of fish chromosomes.
Keywords: Animals; srovnávací genomová hybridizace; Repetitive Sequences, Nucleic Acid; Chromosome Banding; cytogenetické vyšetření; Genomics; genom; Cytogenetic Analysis; Genome; karyotyp; repetitivní sekvence nukleových kyselin; Genetic Variation; sumci; Karyotype; Comparative Genomic Hybridization; hybridizace in situ fluorescenční; zvířata; In Situ Hybridization, Fluorescence; genetická variace; pruhování chromozomů; genomika; Catfishes